Perancangan Aplikasi Mobile Penjualan Ikan Segar Dengan Pendekatan Design Thinking - Muhammad Yordi Septian; Luthfi Dika Chandra; Muhammad Galuh Gumelar; Irma Rasita Gloria Barus; Amata Fami (LPPM STIKI MALANG, 2024)
The decline in aquaculture productivity due to the COVID-19 pandemic and increasing global competition, as well as difficulties for fishermen in selling fish due to high distribution costs and low consumer confidence in fish freshness, demand innovative solutions for the fishing industry. This research aims to answer this problem by developing a mobile-based fresh fish marketing application called